Sunlight exposure behaviour and vitamin D status in photosensitive patients: longitudinal comparative study with healthy individuals at U.K. latitude. (26th October 2014) - Rhodes, L.E.; Webb, A.R.; Berry, J.L.; Felton, S.J.; Marjanovic, E.J.; Wilkinson, J.D.; Vail, A.; Kift, R.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Low vitamin D status in wintertime is prevalent at northerly latitudes. Photosensitive patients are advised to minimize sun exposure, but the impact on the risk of inadequate vitamin D status is unknown. What does this study add? This longitudinal study determined sunlight exposure, photoprotective behaviour and vitamin D status in patients with moderate‐to‐severe photosensitivity in comparison with healthy adults. Patients demonstrated lower weekend ultraviolet B doses, smaller skin area exposure and greater sunscreen use than healthy adults. Photosensitive patients are at high risk of year‐round low vitamin D status, contrasting with seasonal lows in healthy adults, with potential for enhanced adverse health impact.